Exploring the Clinical Landscape of Long Non-coding RNAs in Cancer Diagnosis and Therapy - Riddhiman Bhattacharyya; Soumya Basu; Samir Gupta; Subhayan Sur (Biochemical Genetics, 2026)

Peutz-Jeghers Syndrome and lung cancer: does the risk meet the threshold for lung cancer screening? - Faizah Shareef; Mounica Konjeti; Samir Gupta; Jennifer M. Weiss (Familial Cancer, 2026)
Peutz-Jeghers Syndrome (PJS) is caused by germline pathogenic variants in the STK11 gene and is associated with elevated lifetime risks for several cancers, including lung cancer. Currently, no formal recommendations exist for lung cancer screening in PJS. This structured narrative review compares lung cancer risk in PJS with lung cancer risk in individuals currently eligible for screening based on age and smoking history. PubMed and Web of Science were searched from 1/1/1980 to 9/11/2023 using the terms “Peutz-Jeghers Syndrome” AND “Cancer.” Studies reporting lung cancer risk in PJS were included. Reported lung cancer risks were compared to 5-year, 10-year, and lifetime lung cancer risks in the general population based on age and pack-years of smoking. Seventeen studies were included. Across the studies, the incidence of lung cancer ranged from 0.8 to 13.3%. Studies that included lung cancer risk relative to the general population reported a relative risk range of 2.9–22.9. Cumulative risk was reported in 5 studies and surpassed 5% by age 60 (range 7 to 17%). Guidelines for low-dose CT (LDCT) lung cancer screening for individuals aged 50–80 with a smoking history of at least 20 pack-years are associated with a similar or higher threshold for lung cancer risk. The lifetime lung cancer risk for individuals with PJS is similar to current guideline-based risk thresholds for screening based on age and smoking status. Given their elevated lifetime risk, individuals with PJS may be candidates for LDCT for lung cancer screening and should be formally studied to elucidate the risks, benefits, and optimal implementation in this patient population.

Enhancing deep learning based RMT data inversion using Gaussian random field - Koustav Ghosal; Arun Singh; Samir Malakar; Shalivahan Srivastava; Deepak Gupta (Acta Geophysica, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Targeting the senescence-associated secretory phenotype to modify osteoarthritis in aging - Muhammad Afzal; M. M. Rekha; Samir Sahoo; Surya Nath Pandey; Chandana Maji; Kavita Goyal; Haider Ali; Sachin Kumar Singh; Gaurav Gupta; Md Sadique Hussain (Inflammopharmacology, 2025)

Advancing against drug-resistant tuberculosis: an extensive review, novel strategies and patent landscape - Meghana N. Patel; Archita J. Patel; Manish N. Nandpal; Manan A. Raval; Ravish J. Patel; Amit A. Patel; Keshav Raj Paudel; Philip M. Hansbro; Sachin Kumar Singh; Gaurav Gupta; Kamal Dua; Samir G. Patel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unravelling the role of microneedles in drug delivery: Principle, perspectives, and practices - Molakpogu Ravindra Babu; Sukriti Vishwas; Rubiya Khursheed; Vancha Harish; Anne Boyina Sravani; Farhan Khan; Bader Alotaibi; Abdulkarim Binshaya; John Disouza; Popat S. Kumbhar; Vandana Patravale; Gaurav Gupta; et al. (Drug Delivery and Translational Research, 2024)

Applications and advancements of nanoparticle-based drug delivery in alleviating lung cancer and chronic obstructive pulmonary disease - Gabriele De Rubis; Keshav Raj Paudel; Leander Corrie; Samir Mehndiratta; Vyoma K. Patel; Popat S. Kumbhar; Arehalli Sidramappa Manjappa; John Disouza; Vandana Patravale; Gaurav Gupta; Bikash Manandhar; Rashi Rajput; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Incidences of Helicobacter infection in pigs and tracing occupational hazard in pig farmers - Seema Rani Pegu; Joyshikh Sonowal; Swaraj Rajkhowa; Pranab Jyoti Das; Gyanendra Singh Sengar; Rajib Deb; Manjisa Choudhury; Naba Jyoti Deka; Souvik Paul; Juwar Doley; Dilip Kumar Sarma; Samir Das; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Integrated pretreatment of poplar biomass employing p-toluenesulfonic acid catalyzed liquid hot water and short-time ball milling for complete conversion to xylooligosaccharides, glucose, and native-like lignin - Meysam Madadi; Dan Liu; Yuanhang Qin; Yinchao Zhang; Keikhosro Karimi; Meisam Tabatabaei; Vijai Kumar Gupta; Mortaza Aghbashlo; Zahoor; Sameh Samir Ali (Bioresource Technology, 2023)

Copper-substituted polyoxometalate-soldered interpenetrating polymeric networks membranes for water remediation - Ria Sen Gupta; Samir Mandal; S. Arya; Soumi Dutta; Kunal Manna; Sk. Safikul Islam; Shabnam Pathan; Suryasarathi Bose (Chemical Engineering Journal, 2023)

Clinical efficacy of different monoclonal antibody regimens among non-hospitalised patients with mild to moderate COVID-19 at high risk for disease progression: a prospective cohort study - Alessia Savoldi; Matteo Morra; Pasquale De Nardo; Anna Maria Cattelan; Massimo Mirandola; Vinicio Manfrin; Piergiorgio Scotton; Maria Teresa Giordani; Lucio Brollo; Sandro Panese; Massimiliano Lanzafame; Giovanna Scroccaro; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
This study aimed to compare the clinical progression of COVID-19 in high-risk outpatients treated with the monoclonal antibodies (mAb) bamlanivimab, bamlanivimab-etesevimab and casirivimab-imdevimab. This is an observational, multi-centre, prospective study conducted from 18 March to 15 July 2021 in eight Italian tertiary-care hospitals including mild-to-moderate COVID-19 outpatients receiving bamlanivimab (700 mg), bamlanivimab-etesevimab (700–1400 mg) or casirivimab-imdevimab (1200–1200 mg). All patients were at high risk of COVID-19 progression according to Italian Medicines Agency definitions. In a patient subgroup, SARS-CoV-2 variant and anti-SARS-CoV-2 serology were analysed at baseline. Factors associated with 28-day all-cause hospitalisation were identified using multivariable multilevel logistic regression (MMLR) and summarised with adjusted odds ratio (aOR) and 95% confidence interval (CI). A total of 635 outpatients received mAb: 161 (25.4%) bamlanivimab, 396 (62.4%) bamlanivimab-etesevimab and 78 (12.2%) casirivimab-imdevimab. Ninety-five (15%) patients received full or partial SARS-CoV-2 vaccination. The B.1.1.7 (Alpha) variant was detected in 99% of patients. Baseline serology showed no significant differences among the three mAb regimen groups. Twenty-eight-day all-cause hospitalisation was 11.3%, with a significantly higher proportion ( p 0.001) in the bamlanivimab group (18.6%), compared to the bamlanivimab-etesevimab (10.1%) and casirivimab-imdevimab (2.6%) groups. On MMLR, aORs for 28-day all-cause hospitalisation were significantly lower in patients receiving bamlanivimab-etesevimab (aOR 0.51, 95% CI 0.30–0.88 p 0.015) and casirivimab-imdevimab (aOR 0.14, 95% CI 0.03–0.61, p 0.009) compared to those receiving bamlanivimab. No patients with a history of vaccination were hospitalised. The study suggests differences in clinical outcomes among the first available mAb regimens for treating high-risk COVID-19 outpatients. Randomised trials are needed to compare efficacy of mAb combination regimens in high-risk populations and according to circulating variants.

Bacterial diversity associated with a newly described bioeroding sponge, Cliona thomasi, from the coral reefs on the West Coast of India - Sambhaji Mote; Vishal Gupta; Kalyan De; Mandar Nanajkar; Samir R. Damare; Baban Ingole (Folia Microbiologica, 2021)

Mapping QTLs for 15 morpho-metric traits in Arabidopsis thaliana using Col-0 × Don-0 population - Astha Gupta; Vandana Jaiswal; Samir V. Sawant; Hemant Kumar Yadav (Physiology and Molecular Biology of Plants, 2020)

Pollen and spores in yellow rain from Lucknow, northern India - Samir Kumar Bera; Swati Tripathi; Sateesh Chandra Gupta; Sneha Bera (Palynology, 2018)

Somatic PI3K activity regulates transition to the spermatocyte stages in Drosophila testis - Samir Gupta; Krishanu Ray (Journal of Biosciences, 2017)

A prognostic model for advanced colorectal neoplasia recurrence - Lin Liu; Karen Messer; John A. Baron; David A. Lieberman; Elizabeth T. Jacobs; Amanda J. Cross; Gwen Murphy; Maria Elena Martinez; Samir Gupta (Cancer Causes & Control, 2016)

Delivery of Exenatide and Insulin Using Mucoadhesive Intestinal Devices - Vivek Gupta; Byeong-Hee Hwang; Nishit Doshi; Amrita Banerjee; Aaron C. Anselmo; Samir Mitragotri (Annals of Biomedical Engineering, 2016)

Screening of a library of 4-aryl/heteroaryl-4H-fused pyrans for xanthine oxidase inhibition: synthesis, biological evaluation and docking studies - Ramandeep Kaur; Fatima Naaz; Sahil Sharma; Samir Mehndiratta; Manish Kumar Gupta; Preet Mohinder Singh Bedi; Kunal Nepali (Medicinal Chemistry Research, 2015)

Genomic-derived microsatellite markers for diversity analysis in Jatropha curcas - Ramanuj Maurya; Astha Gupta; Sunil Kumar Singh; Krishan Mohan Rai; Chandrawati; Ratna Katiyar; Samir V. Sawant; Hemant Kumar Yadav (Trees, 2015)

Levels of Heavy Metals and Essential Minerals in Hair Samples of Children with Autism in Oman: a Case–Control Study - Yahya M. Al-Farsi; Mostafa I. Waly; Marwan M. Al-Sharbati; Mohammed A. Al-Shafaee; Omar A. Al-Farsi; Maha M. Al-Khaduri; Ishita Gupta; Allal Ouhtit; Samir Al-Adawi; Mona F. Al-Said; Richard C. Deth (Biological Trace Element Research, 2013)

Pharmacokinetics, safety, and tolerability of ribavirin in hemodialysis-dependent patients - Samir K. Gupta; Bhavna Kantesaria; Paul Glue (European Journal of Clinical Pharmacology, 2012)

Effects of multiple-dose pegylated interferon alfa-2b on the activity of drug-metabolizing enzymes in persons with chronic hepatitis C - Samir K. Gupta; Karen Kolz; David L. Cutler (European Journal of Clinical Pharmacology, 2011)

Complete sequence and organisation of the Jatropha curcas (Euphorbiaceae) chloroplast genome - Mehar H. Asif; Shrikant S. Mantri; Ayush Sharma; Anukool Srivastava; Ila Trivedi; Priya Gupta; Chandra S. Mohanty; Samir V. Sawant; Rakesh Tuli (Tree Genetics & Genomes, 2010)

Risk of pancreatic cancer by alcohol dose, duration, and pattern of consumption, including binge drinking: a population-based study - Samir Gupta; Furong Wang; Elizabeth A. Holly; Paige M. Bracci (Cancer Causes & Control, 2010)

Pancreatitis and pancreatic cancer in two large pooled case–control studies - Paige M. Bracci; Furong Wang; Manal M. Hassan; Samir Gupta; Donghui Li; Elizabeth A. Holly (Cancer Causes & Control, 2009)

Conserved nucleotide sequences in highly expressed genes in plants - Samir V. Sawant; Pradhyumna K. Singh; Shiv K. Gupta; Raju Madnala; Rakesh Tuli (Journal of Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)